2022
DOI: 10.2196/34088
|View full text |Cite
|
Sign up to set email alerts
|

System-Level Factors Associated With Telephone and Video Visit Use: Survey of Safety-Net Clinicians During the Early Phase of the COVID-19 Pandemic

Abstract: Background The COVID-19 pandemic prompted safety-net health care systems to rapidly implement telemedicine services with little prior experience, causing disparities in access to virtual visits. While much attention has been given to patient barriers, less is known regarding system-level factors influencing telephone versus video-visit adoption. As telemedicine remains a preferred service for patients and providers, and reimbursement parity will not continue for audio visits, health systems must ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…Callison et al18 used interrupted time series methods to examine telemedicine use among Medicaid beneficiaries before and during the pandemic and found that the outpatient service use disparities between White and Black Louisiana Medicaid beneficiaries, but gaps in telemedicine use occurred at the same time. They also find that Latino beneficiaries had large reductions in outpatient service use and relatively small increases in telemedicine use compared with other populations, consistent with past research that highlights barriers to care due to limited English language proficiency 3,12,13…”
Section: Commentarysupporting
confidence: 80%
See 2 more Smart Citations
“…Callison et al18 used interrupted time series methods to examine telemedicine use among Medicaid beneficiaries before and during the pandemic and found that the outpatient service use disparities between White and Black Louisiana Medicaid beneficiaries, but gaps in telemedicine use occurred at the same time. They also find that Latino beneficiaries had large reductions in outpatient service use and relatively small increases in telemedicine use compared with other populations, consistent with past research that highlights barriers to care due to limited English language proficiency 3,12,13…”
Section: Commentarysupporting
confidence: 80%
“…Community health centers (CHC) struggle with addressing racial-ethnic and linguistic disparities in telemedicine access 11. CHCs and other organizations serving socioeconomically vulnerable populations face barriers to implementing telemedicine due to billing challenges, required technology and workflow changes, and unstable, low-quality internet connections for some patients 12–16. Despite this, CHCs accelerated telemedicine implementation during the pandemic,17 but the rapid expansion may have not supported high-quality clinical interactions given the predominant use of audio-only visits in these settings.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…The training issues highlighted by the doctors are important. Other studies have found that peer training is useful to introduce non-early adopter GPs to video consulting (16), and that there is a correlation between a desire for more training and the non-adoption of video consulting (17).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Visual cues aid communication and improve the rapport between the patient and physician. Clinicians have also seen that video-enabled picking up on nonverbal cues during visits, compared with telephone contact and visual contact with patients, also reduces the risk of miscommunication (11,12).…”
Section: Introductionmentioning
confidence: 99%